The impact of Sino-Afro Economic Cooperation on presidential trust in Africa - Zainuddin, Nur Najiha Zahiera (2019)
China’s influence in the world is undoubtedly spreading in various regions in both terms politically and economically. The rise of China has proven the capability of the socialist government in bringing the nation to super power level in a very short period of time. However, China’s growth is not impressive merely because about the GDP’s numbers but more importantly towards the application of their innovative economic model. Due to this, many developing countries displayed favour in Chinese economic model compared to many pro-democracy and free market Western style of economic model. Among many countries, African leaders has expressed the highest interest in welcoming Chinese investors in their country. In addition to that, due to Africa’s rich of natural resources and its untapped market potential, China sees Africa as a good long term partner and is willing to invest high amount of money to develop the region which is what many of the African nations are in need for. However, this research in interested in the public’s opinion towards the Chinese investment through the assessment of the trust level in their president. Political trust is a tool of measurement in determine the public’s view towards the effectiveness of an institution, in this case, the president. The president plays a vital role in allowing the amount of Chinese influence presence in their country through their policies in accepting or rejecting Chinese investors. Hence, it would be interesting to see if the involvement of China will impact the public’s trust towards their own presidents.